IgA Immune Complexes Induce Osteoclast-Mediated Bone Resorption - Breedveld, Annelot C.; van Gool, Melissa M. J.; van Delft, Myrthe A. M.; van der Laken, Conny J.; de Vries, Teun J.; Jansen, Ineke D. C.; van Egmond, Marjolein (Frontiers in Immunology, 2021)
Objective: Autoantibodies are detected in most patients with rheumatoid arthritis (RA) and can be of the IgM, IgG or IgA subclass. Correlations between IgA autoantibodies and more severe disease activity have been previously reported, but the functional role of IgA autoantibodies in the pathogenesis of RA is ill understood. In this study, we explored the effect of IgA immune complexes on osteoclast mediated bone resorption. Methods: Anti-citrullinated peptide antibody (ACPA) and anti-carbamylated protein (anti-CarP) antibody levels of the IgA and IgG isotype and rheumatoid factor (RF) IgA were determined in synovial fluid (SF) of RA patients. Monocytes, neutrophils, and osteoclasts were stimulated with precipitated immune complexes from SF of RA patients or IgA- and IgG-coated beads. Activation was determined by neutrophil extracellular trap (NET) release, cytokine secretion, and bone resorption were used as a readout for activation. Results: NET formation by neutrophils was enhanced by SF immune complexes compared to immune complexes from healthy or RA serum. Monocytes stimulated with isolated SF immune complexes released IL-6 and IL-8, which correlated with the levels of ACPA IgA levels in SF. Osteoclasts cultured in the presence of supernatant of IgA-activated monocytes resorbed significantly more bone compared to osteoclasts that were cultured in supernatant of IgG-activated monocytes (p=0.0233). Osteoclasts expressed the Fc receptor for IgA (FcαRI; CD89) and Fc gamma receptors. IgA-activated osteoclasts however produced significantly increased levels of IL-6 (p<0.0001) and IL-8 (p=0.0007) compared to IgG-activated osteoclasts. Both IL-6 (p=0.03) and IL-8 (p=0.0054) significantly enhanced bone resorption by osteoclasts. Conclusion: IgA autoantibodies induce release of IL-6 and IL-8 by immune cells as well as osteoclasts, which enhances bone resorption by osteoclasts. We anticipate that this will result in more severe disease activity in RA patients. Targeting IgA-FcαRI interactions therefore represents a promising novel therapeutic strategy for RA patients with IgA autoantibodies.